Universal Electrocardiographic Screening for Long QT Syndrome in Hospitalized Neonates - Kaemingk, Bethany D.; Ulrich, Timothy J.; Li, Man; Carey, William A.; Ellsworth, Marc A. (American Journal of Perinatology, 2020)
Objective Long QT syndrome (LQTS) is a known cause of unexpected death, leading some to recommend routine neonatal electrocardiographic (ECG) screening. We used continuous electronic heart rate corrected QT interval (QTc) monitoring to screen for interval prolongation in a cohort of hospitalized neonates to identify those at a risk of having LQTS. We hypothesized that this screening method would yield an acceptable positive predictive value (PPV).Study Design A cohort of 589 infants hospitalized in a level II neonatal intensive care unit were screened through continuous electronic QTc monitoring linked to an investigator-designed, computerized data sniffer. Screening was conducted from days-of-life 3 through 7 or until hospital discharge. The data sniffer alerted investigators for a 24-hour average QTc of ≥475 ms. Positively screened patients were further evaluated with 12-lead ECG.Results Positive screens were obtained in 5.6% of patients, all of whom had negative follow-up ECG testing (PPV = 0%). Furthermore, one-quarter of positively screened neonates underwent echocardiography based on ECG findings, none of which identified clinically relevant pathology.Conclusion Electronic monitoring of QTc in hospitalized neonates during the first week of life was not an efficient way to identify those at a risk of having LQTS. Conversely, screening triggered unnecessary testing.
Keywords: infant; electrocardiogram; long QT syndrome; neonatal intensive care units; cardiac electrophysiology